Right to intercultural bilingual education for indigenous children in Peru: progress and challenges - Rebaza Vílchez, Karen Maribel (2018)
Peru is a pluricultural and multilingual country inhabited by 55 indigenous or indigenous peoples (51 Amazonian and 4 Andean peoples) who speak a total of 47 indigenous languages, according to the Official Database of Indigenous Peoples of the Ministry of Culture of Peru. Moreover, according to the National Institute of Statistics and Informatics (INEI), the number of children and adolescents whose mother tongue is indigenous amounts to approximately 2 million, representing 8% of the national population. This diversity represents a challenge for the Peruvian State in the educational formation of basic and superior quality. In this context, this article aims to analyze the legal treatment, state advances and challenges in guaranteeing the right to bilingual intercultural education of Peruvian indigenous children.